Discourse on Providing Fair Housing for The Middle Class: Housing Preferences of Young Lecturers in Peri-Urban Areas - Amelia Tri Widya; Stirena Rossy Tamariska; Antusias Nurzukhrufa; Yemima Sahmura Vividia (Talenta Publisher, 2026)
Indonesia's middle class, which comprises 66.35% of the total population and contributes 81.49% to national consumption, faces serious challenges in accessing decent housing in urban areas. Young middle-class individuals face housing unaffordability due to an 11.19% increase in housing prices over the past five years, while government housing policies still focus on Low-Income Communities, leaving the middle class as the